2010
DOI: 10.1111/j.1423-0410.2009.01285.x
|View full text |Cite
|
Sign up to set email alerts
|

Capillary and venous haemoglobin levels in blood donors: a 42-month study of 36 258 paired samples

Abstract: Capillary haemoglobin levels of 12.0-12.5 g/dl in healthy females or 13.0-13.5 g/dl in healthy males are substantively equivalent to venous haemoglobin levels of > or = 12.5 and > or = 13.5 g/dl for women and men respectively. This finding has permitted an additional 32 990 blood units to be collected over the period of the study, a gain of 9.4%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 17 publications
7
44
0
Order By: Relevance
“…This disparity may be explained by the fact that men have been shown to have higher circulating hemoglobin levels, 24 and thus a greater reserve before reaching the transfusion threshold. Conclusively, there is still no clear evidence regarding whether there are gender-specific differences in risk for transfusion, and further evaluation is needed.…”
Section: Gendermentioning
confidence: 97%
“…This disparity may be explained by the fact that men have been shown to have higher circulating hemoglobin levels, 24 and thus a greater reserve before reaching the transfusion threshold. Conclusively, there is still no clear evidence regarding whether there are gender-specific differences in risk for transfusion, and further evaluation is needed.…”
Section: Gendermentioning
confidence: 97%
“…3 We have now shown that the gap is under physiologic control and is The mean difference and standard error between venous and capillary hemoglobin levels (⌬VC) in 35 985 paired capillary and venous samples were taken from 25 557 females and 10 428 males in whom the capillary hemoglobin was Ͼ 11.5 to Ͻ 12.5 g/dL and Ͼ 12.5 to Ͻ 13.5 g/dL, respectively, and from 81 male and 74 female first-time blood donors where the capillary hemoglobin levels were above the cutoff for inclusion in the original study group. 1 There is a significant change comparing lower capillary Hb with higher venous Hb (by Kruskal-Wallis, followed by Dunn posttest). The ⌬VC increases in a linear manner as measured by Spearman correlation, in both females and males as the capillary hemoglobin levels in the groups decline (r ϭ Ϫ0.9879, P Ͻ .0001 for the female group; r ϭ Ϫ0.9152, P ϭ .0005 for the male group).…”
mentioning
confidence: 92%
“…1 Subsequently we have observed that the gap between the capillary and venous hemoglobin levels decreased both in males and in females as the hemoglobin level increased. In addition, the curves for males and females were parallel: they did not overlap ( Figure 1A).…”
mentioning
confidence: 93%
“…The cuvettes containing the working reagent have a limited temperature range for storage, necessitating processes for material management, which can be problematic, particularly on mobile collection sites. Operator variability, sample site, seasonal and postural factors [11][12][13] have all been demonstrated to influence results. Additionally, a substantial percentage of capillary haemoglobin values have been shown to be lower than those obtained from venous blood [11,14], which may result in unnecessary deferral of blood donors.…”
Section: Limitations Of Current Screening Technologymentioning
confidence: 99%
“…Operator variability, sample site, seasonal and postural factors [11][12][13] have all been demonstrated to influence results. Additionally, a substantial percentage of capillary haemoglobin values have been shown to be lower than those obtained from venous blood [11,14], which may result in unnecessary deferral of blood donors. These caveats emphasise the importance of validation, quality control and training.…”
Section: Limitations Of Current Screening Technologymentioning
confidence: 99%